OVERCOMING BARRIERS TO CROSS-CULTURAL COMMUNICATION IN A MULTINATIONAL ENVIRONMENT - Melyana R Pugu; Suroso; Andrias Chandra Putra Dewanto (ADISAM PUBLISHER, 2024)
The research aims to identify and solve challenges in cross-cultural communication in a multinational environment. With sustainable global change and a push for inclusiveness and diversity, it is important to understand and bridge cultural differences. The study explores strategies to overcome communication barriers and facilitate more effective collaboration. The research method used is qualitative, using literary research as its primary method. The results of this study show that overcoming the barriers to cross-cultural communication requires appropriate strategies. These efforts include cultivating respect and awareness of other cultures, preparing effective translations to overcome language barriers, using appropriate communication technologies, promoting inclusiveness and participation of all team members, and conducting regular evaluations and feedback. Thus, organizations can create a conducive working environment that supports productivity, innovation, and effective teamwork